Morphological characteristic of purple long yard bean cultivars and their tolerance to drought stress - Lestari, M W; Kuswanto, K; Wardiyati, T; Widoretno, W (Brawijaya University, 2015)
The cultivation of purple long yard bean which tolerance to drought stress and have high productivity can improve farming in arid area. The purpose of this study was to evaluate the mechanism of the tolerance purple long yard beans to drought stress based on morphologic characters, to get the hypothesis method of tolerance and to obtain tolerance cultivars to the drought stress. Eight cultivars of purple long yard beans, i.e. UBPHU1-41, UBPHU1-130, UBPU3-153, UBPU1-202, UBPU2-222, UBPU1-365, Brawijaya 4 and Bagong 2, were tested in two environmental conditions, 100% field capacity and 50% field capacity. The results showed that drought stress in purple long yard bean affected all morphological characters observed, except for root length and flowering time. Estimation of tolerance to drought stress using the Principles Component Analysis (PCA) showed that the shoot fresh weight could be an indicator of purple pod bean tolerance to drought stress. However, the test using Stress Susceptibility Index (SSI) was not able to classify the purple long yard bean tolerance to drought stress. The results of analysis using PCA followed by discriminant analysis and clustering dendrogram showed that the UBPU1-41, UBPU1-130, UBPU2-222, UBPU1-365, UB4 and Bagong 2 cultivars were medium cultivars that are tolerant to drought stress. Therefore, they can be planted in semiarid regions.